Chirale polyzyklische aromatische Kohlenwasserstoffe mit Affensattel-Topologie [data] - Kirschbaum, Tobias (Universität, 2022)
In this thesis, the first chiral polycyclic aromatic hydrocarbon (PAH) with a monkey saddle topology is presented. Starting from a truxene building...
Gesehen am 07.12.2022
Keywords: Forschungsdaten; Datenbank